Composite coating for heat dissipation of box transformer substation and preparation method of composite coating
By spraying a composite coating containing polyether modified epoxy resin and nanoceramic heat dissipation filler on the surface of the box change equipment, the problem of insufficient heat dissipation of the box change equipment in high temperature environments is solved, and the effect of effective cooling and improving equipment stability is achieved.
Patent Information
- Application Number
- CN202411974521.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
Box transformer equipment is prone to excessive temperature, system error alarm, display screen, fan shutdown and other faults in high temperature environments, and traditional cooling methods require additional space and energy, which makes maintenance costs high.
A composite coating is prepared by stirring and ball milling to form a coating with good thermal conductivity and heat dissipation properties.
It significantly improves the thermal conductivity and heat dissipation performance of nanoceramic composite coatings, effectively reduces the internal temperature of the equipment, maintains good adhesion and salt spray corrosion resistance, and meets the requirements of stability and reliability.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating processing, and in particular to a composite coating for heat dissipation of a box transformer and a preparation method thereof. Background Art
[0002] With the rapid development of the economy, the national electricity consumption has continued to surge, and higher requirements have been placed on the stability of the power system. As an important part of the power system, the box transformer provides an important guarantee for the stable operation of the system. Most box transformers are installed in open outdoor locations. Due to the high heat generated by the equipment itself and the influence of the high temperature of the environment, the internal temperature is very high. This high temperature will not only cause a decrease in work efficiency, stability and life, but also in the continuous high temperature weather in summer, the box transformer is prone to overtemperature, system false alarms, display screen flower screen, fan stop and other faults. These faults increase the workload of operation and maintenance personnel, and may also cause large economic losses and power grid safety accidents.
[0003] In the face of the above situation, it is particularly important to take effective heat dissipation and cooling measures as well as to protect the equipment. Although traditional cooling methods such as increasing ventilation or using cooling devices are effective, they often require additional space and energy consumption, and have high maintenance costs. In contrast, spraying functional coatings on the surface of the equipment is a simpler and more efficient method. This type of functional coating can not only protect the equipment from external environmental factors such as ultraviolet rays, moisture and corrosion, but also greatly improve the heat dissipation performance of the equipment, improve operating efficiency and stability. Although some existing patents have disclosed that ceramic coatings have good thermal conductivity and heat dissipation capabilities, their adhesion and salt spray resistance are relatively poor in some application scenarios, which seriously affects their service life, and still needs further improvement and enhancement. Summary of the invention
[0004] The purpose of the present invention is to propose a composite coating for box-type transformer heat dissipation and a preparation method thereof, so as to solve the technical problem of how to improve the heat dissipation and protection of the box-type transformer.
[0005] As one aspect of the present invention, a composite coating for heat dissipation of a box transformer is provided, which comprises the following raw materials in parts by weight:
[0006] 40-50 parts of epoxy resin, 2-8 parts of polyether modified epoxy resin, 10-20 parts of nano ceramic heat dissipation filler, 0.2-0.5 parts of defoaming agent, 0.1-0.3 parts of wetting agent, 0.1-0.3 parts of leveling agent, 2-8 parts of curing agent, and 40-60 parts of water.
[0007] Preferably, the polyether-modified epoxy resin is a mixture of epoxy resin, polypropylene glycol monomethyl ether and tetrabutylammonium bromide.
[0008] Preferably, the nano-ceramic heat dissipation filler is a mixture of oxide composite nano-ceramics, nitride composite nano-ceramics and dopamine hydrochloride.
[0009] Preferably, the curing agent is any one or more of N-aminoethylpiperazine, m-phenylenediamine, and diethylenetriamine.
[0010] As another aspect of the present invention, a method for preparing a composite coating is also provided, which is used to prepare the composite coating for heat dissipation of a box-type transformer, and comprises the following steps:
[0011] According to the component formula, epoxy resin, polyether modified epoxy resin, defoamer, wetting agent, leveling agent and water are mixed and stirred; after adding nano ceramic heat dissipation filler and continuing to stir, curing agent is added and mixed until uniform, so as to obtain a composite coating for box-type transformer heat dissipation.
[0012] Preferably, the method further comprises mixing 6-8 parts by weight of epoxy resin with 7-10 parts by weight of polypropylene glycol monomethyl ether, adding 0.1-0.2 parts by weight of tetrabutylammonium bromide at 60-70° C. under nitrogen protection, heating to 100-110° C., and reacting for 5-10 hours to obtain a polyether-modified epoxy resin.
[0013] Preferably, the method further comprises the steps of mixing lithium hydroxide with an ethanol aqueous solution, adding hexagonal boron nitride under stirring conditions, and sequentially subjecting the mixture to a temperature-raising reaction, cooling, filtering, washing with water, and drying to obtain pretreated hexagonal boron nitride;
[0014] Pretreated hexagonal boron nitride and γ-mercaptopropyltrimethoxysilane are added to an isopropanol aqueous solution and subjected to ultrasonication, and then nano-aluminum nitride and carbon nanotubes are added and the mixture is ball-milled, filtered, and dried in sequence to obtain a nitride composite nano-ceramic.
[0015] Aluminum nitrate, magnesium nitrate, zinc nitrate, zirconium nitrate and yttrium nitrate are added to water and ultrasonicated, and then gluconic acid is added and heated, stirred, dried and calcined in sequence to obtain oxide composite nano-ceramics;
[0016] The oxide composite nano-ceramics and the nitride composite nano-ceramics are added to a buffer solution and ultrasonicated, then dopamine hydrochloride is added and the mixture is heated for reaction, cooled, filtered, washed with water, and dried in sequence to obtain a nano-ceramic heat dissipation filler.
[0017] Preferably, the method further comprises the steps of mixing 0.03-0.06 parts by weight of lithium hydroxide with 250-350 parts by weight of a 40-50 wt% ethanol aqueous solution, adding 10-20 parts by weight of hexagonal boron nitride under stirring conditions, continuing stirring for 15-30 minutes, and heating to 290-305° C. to react for 1-3 hours;
[0018] After the reaction is finished, cooling, filtering, washing and drying are performed in sequence to obtain pretreated hexagonal boron nitride;
[0019] 1-2 parts by weight of pretreated hexagonal boron nitride and 0.1-0.3 parts by weight of γ-mercaptopropyltrimethoxysilane are added to 25-40 parts by weight of isopropanol aqueous solution and ultrasonicated for 15-30 minutes, then 0.4-0.6 parts by weight of nano aluminum nitride and 0.1-0.3 parts by weight of carbon nanotubes are added and ball-milled for 10-15 hours. After the ball-milling is completed, filtering and drying are performed in sequence to obtain nitride composite nano-ceramics.
[0020] Preferably, the method further comprises the steps of adding 2-5 parts by weight of aluminum nitrate, 1-2 parts by weight of magnesium nitrate, 1-2 parts by weight of zinc nitrate, 0.2-0.4 parts by weight of zirconium nitrate and 0.1-0.3 parts by weight of yttrium nitrate to 150-300 parts by weight of water, ultrasonicating for 10-20 minutes, adding 20-30 parts by weight of gluconic acid, stirring for 100-150 minutes at 65-70° C., drying, heating to 600-700° C. and calcining for 130-160 minutes to obtain oxide composite nanoceramics.
[0021] Preferably, the method further comprises the steps of adding 1-3 parts by weight of oxide composite nanoceramics and 1-2 parts by weight of nitride composite nanoceramics into 80-120 parts by weight of buffer solution, ultrasonicating for 30-50 minutes, adding 1-2 parts by weight of dopamine hydrochloride, reacting at 60-65° C. for 15-20 hours, cooling, filtering, washing with water and drying once to obtain the nanoceramic heat dissipation filler.
[0022] In summary, the implementation of the embodiments of the present invention has the following beneficial effects:
[0023] The composite coating for heat dissipation of box transformers provided by the present invention and the preparation method thereof, by using polyether modified epoxy resin and specific nano ceramic heat dissipation filler in the coating component formula, significantly improves the thermal conductivity and heat dissipation performance of the nano ceramic composite coating, can be used on power distribution equipment such as box transformers, effectively reduce the temperature inside the equipment, and still have good adhesion and salt spray corrosion resistance in harsh outdoor use environments, and can meet the requirements of stability and reliability. The present invention also provides a preparation process for the above nano ceramic composite coating, which is simple. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in further detail below.
[0025] The present invention provides an embodiment of a composite coating for heat dissipation of a box-type transformer. In this embodiment, the composite coating comprises the following raw materials in parts by weight:
[0026] 40-50 parts of epoxy resin, 2-8 parts of polyether modified epoxy resin, 10-20 parts of nano ceramic heat dissipation filler, 0.2-0.5 parts of defoaming agent, 0.1-0.3 parts of wetting agent, 0.1-0.3 parts of leveling agent, 2-8 parts of curing agent, and 40-60 parts of water.
[0027] In one embodiment, the polyether-modified epoxy resin is a mixture of epoxy resin, polypropylene glycol monomethyl ether and tetrabutylammonium bromide. The polyether-modified epoxy resin is prepared by reacting epoxy resin, polypropylene glycol monomethyl ether and tetrabutylammonium bromide as raw materials.
[0028] In one embodiment, the nano ceramic heat dissipation filler is a mixture of oxide composite nano ceramics, nitride composite nano ceramics and dopamine hydrochloride. The nano ceramic heat dissipation filler is made by reacting oxide composite nano ceramics, nitride composite nano ceramics and dopamine hydrochloride as raw materials.
[0029] In one embodiment, the curing agent is any one or more of N-aminoethylpiperazine, m-phenylenediamine, and diethylenetriamine.
[0030] It should be noted that the defoamer is any one of BYK-028 defoamer, BYK-022 defoamer and BYK-015 defoamer. The wetting agent is any one of BYK-378 wetting agent, BYK-346 wetting agent and BYK-310 wetting agent. The leveling agent is any one of BYK-381 leveling agent, BYK-377 leveling agent and BYK-326 leveling agent.
[0031] The present invention also provides a method for preparing a composite coating, which is used to prepare the composite coating for heat dissipation of a box-type transformer, and comprises the following steps:
[0032] According to the component formula, epoxy resin, polyether modified epoxy resin, defoamer, wetting agent, leveling agent and water are mixed and stirred; after adding nano ceramic heat dissipation filler and continuing to stir, curing agent is added and mixed until uniform, so as to obtain a composite coating for box-type transformer heat dissipation.
[0033] One embodiment further includes the following steps: mixing 6-8 parts by weight of epoxy resin with 7-10 parts by weight of polypropylene glycol monomethyl ether, adding 0.1-0.2 parts by weight of tetrabutylammonium bromide at a temperature of 60-70° C. under nitrogen protection, heating to 100-110° C., and reacting for 5-10 hours to obtain a polyether-modified epoxy resin.
[0034] One embodiment further includes the following steps: mixing lithium hydroxide with an ethanol aqueous solution, adding hexagonal boron nitride under stirring conditions, and sequentially subjecting the mixture to a temperature reaction, cooling, filtering, washing with water, and drying to obtain pretreated hexagonal boron nitride; adding the pretreated hexagonal boron nitride and γ-mercaptopropyltrimethoxysilane to an isopropanol aqueous solution for ultrasonication, adding nano-aluminum nitride and carbon nanotubes, and sequentially subjecting the mixture to ball milling, filtering, and drying to obtain a nitride composite nano-ceramic; adding aluminum nitrate, magnesium nitrate, zinc nitrate, zirconium nitrate, and yttrium nitrate to water for ultrasonication, adding gluconic acid, and sequentially subjecting the mixture to heating, stirring, drying, and calcining to obtain an oxide composite nano-ceramic; adding the oxide composite nano-ceramic and the nitride composite nano-ceramic to a buffer solution for ultrasonication, adding dopamine hydrochloride, and sequentially subjecting the mixture to a heating reaction, cooling, filtering, washing with water, and drying to obtain a nano-ceramic heat dissipation filler.
[0035] The method comprises the following steps: mixing 0.03-0.06 parts by weight of lithium hydroxide with 250-350 parts by weight of a 40-50wt% ethanol aqueous solution, adding 10-20 parts by weight of hexagonal boron nitride under stirring conditions, continuing stirring for 15-30 minutes, heating to 290-305° C. and reacting for 1-3 hours; after the reaction is completed, cooling, filtering, washing and drying are performed in sequence to obtain pretreated hexagonal boron nitride; adding 1-2 parts by weight of pretreated hexagonal boron nitride and 0.1-0.3 parts by weight of γ-mercaptopropyltrimethoxysilane to 25-40 parts by weight of an isopropanol aqueous solution and ultrasonicating for 15-30 minutes, adding 0.4-0.6 parts by weight of nano aluminum nitride and 0.1-0.3 parts by weight of carbon nanotubes and ball milling for 10-15 hours, and after the ball milling is completed, filtering and drying are performed in sequence to obtain a nitride composite nano-ceramic.
[0036] 2-5 parts by weight of aluminum nitrate, 1-2 parts by weight of magnesium nitrate, 1-2 parts by weight of zinc nitrate, 0.2-0.4 parts by weight of zirconium nitrate and 0.1-0.3 parts by weight of yttrium nitrate are added to 150-300 parts by weight of water and ultrasonicated for 10-20 minutes, then 20-30 parts by weight of gluconic acid are added, stirred for 100-150 minutes at 65-70° C., dried, heated to 600-700° C. and calcined for 130-160 minutes to obtain oxide composite nanoceramics.
[0037] One embodiment further includes the following steps: adding 1-3 parts by weight of oxide composite nanoceramics and 1-2 parts by weight of nitride composite nanoceramics into 80-120 parts by weight of buffer solution, ultrasonicating for 30-50 minutes, adding 1-2 parts by weight of dopamine hydrochloride, reacting at 60-65° C. for 15-20 hours, cooling, filtering, washing with water, and drying once to obtain a nanoceramic heat dissipation filler.
[0038] Specifically, in Example 1, a composite coating is made of the following components in parts by weight:
[0039] 45 parts by weight of bisphenol A liquid epoxy resin, 5 parts by weight of polyether modified epoxy resin, 15 parts by weight of nano ceramic heat dissipation filler, 0.4 parts by weight of defoamer, 0.15 parts by weight of wetting agent, 0.25 parts by weight of leveling agent, 5 parts by weight of curing agent, and 50 parts by weight of water. The defoamer is BYK-028 defoamer; the wetting agent is BYK-378 wetting agent; the leveling agent is BYK-381 leveling agent; and the curing agent is N-aminoethylpiperazine.
[0040] The preparation method of the polyether modified epoxy resin is as follows: 7.2 parts by weight of bisphenol A liquid epoxy resin and 8 parts by weight of polypropylene glycol monomethyl ether are mixed, 0.12 parts by weight of tetrabutylammonium bromide is added at 60°C under nitrogen protection, the temperature is raised to 105°C for reaction for 7 hours, and the heating rate is 5°C / min to obtain the polyether modified epoxy resin. The bisphenol A liquid epoxy resin adopts epoxy resin E-51, with an epoxy equivalent of 180-200g / mol and a viscosity (25°C) of 8000-16000mPa·s; the polypropylene glycol monomethyl ether has an average molecular weight of 800 and a hydroxyl value of 65-75mgKOH / g.
[0041] The preparation method of the nano ceramic heat dissipation filler is as follows: 0.056 parts by weight of lithium hydroxide is mixed with 300 parts by weight of a 45wt% ethanol aqueous solution, 15 parts by weight of hexagonal boron nitride is added under stirring conditions of 700r / min and stirring is continued for 20min, the temperature is raised to 300°C for reaction for 2h, the heating rate is 5°C / min, after the reaction is completed, the mixture is cooled to room temperature, filtered, washed with water until neutral, and vacuum dried to obtain pretreated hexagonal boron nitride; 1.5 parts by weight of pretreated hexagonal boron nitride and 0.2 parts by weight of γ-mercaptopropyltrimethoxysilane are added to 30 parts by weight of a 30wt% isopropanol aqueous solution and ultrasonicated for 20min n, the ultrasonic frequency is 35kHz, the ultrasonic power is 200W, and then 0.5 weight parts of nano aluminum nitride and 0.2 weight parts of carbon nanotubes are added and ball-milled for 12 hours, filtered after the end, and vacuum dried to obtain nitride composite nanoceramics; wherein, the ball milling speed is 500r / min, the ball milling medium is composed of zirconia balls with a diameter of 1mm and zirconia balls with a diameter of 10mm in a mass ratio of 1:0.2, and the ball-to-material ratio is 15:1; the average particle size of the nano aluminum nitride is 50nm; the carbon nanotubes are single-walled carbon nanotubes prepared by chemical vapor deposition, with a tube diameter of 2nm and a tube length of 50μm;
[0042] 3 parts by weight of aluminum nitrate, 1.5 parts by weight of magnesium nitrate, 1.5 parts by weight of zinc nitrate, 0.3 parts by weight of zirconium nitrate and 0.2 parts by weight of yttrium nitrate are added to 200 parts by weight of water and ultrasonicated for 15 minutes at an ultrasonic frequency of 35kHz and an ultrasonic power of 200W, then 25 parts by weight of gluconic acid are added, and the mixture is stirred at 68°C and 120r / min for 120 minutes to evaporate water, and then freeze-dried and heated to 650°C for calcination for 150 minutes at a heating rate of 5°C / min to obtain oxide composite nanoceramics; 2 parts by weight of oxide composite nanoceramics and 1.5 parts by weight of nitride composite nanoceramics are added to 100 parts by weight of Tris buffer (pH 8.5) and ultrasonicated for 40 minutes at an ultrasonic frequency of 35kHz and an ultrasonic power of 200W, and then 1.5 parts by weight of dopamine hydrochloride are added, and the mixture is reacted at 63°C for 18 hours, and then cooled to room temperature, filtered, washed with water until neutral, and vacuum dried to obtain nanoceramic heat dissipation filler.
[0043] The preparation process corresponding to the above embodiment 1 comprises the following steps:
[0044] According to the component formula, bisphenol A liquid epoxy resin, polyether modified epoxy resin, defoamer, wetting agent, leveling agent and water are mixed, stirred at 500r / min for 20min, then nano-ceramic heat dissipation filler is added and stirred for 10min, and then curing agent is added and mixed evenly to obtain the nano-ceramic composite coating.
[0045] In Example 1, a composite coating is prepared by including the following components in parts by weight:
[0046] 40 parts by weight of epoxy resin, 2 parts by weight of polyether modified epoxy resin, 10 parts by weight of nano ceramic heat dissipation filler, 0.2 parts by weight of defoamer, 0.1 parts by weight of wetting agent, 0.1 parts by weight of leveling agent, 2 parts by weight of curing agent, 40 parts by weight of water. The defoamer is BYK-028 defoamer; the wetting agent is BYK-378 wetting agent; the leveling agent is BYK-381 leveling agent; the curing agent is N-aminoethylpiperazine. The bisphenol A type liquid epoxy resin uses epoxy resin E-51, the epoxy equivalent is 180-200g / mol, and the viscosity (25°C) is 8000-16000mPa·s.
[0047] The preparation method of the polyether-modified epoxy resin is the same as that in Example 1.
[0048] The preparation method of the nano ceramic heat dissipation filler is the same as that of Example 1.
[0049] The preparation process corresponding to the above embodiment 2 comprises the following steps:
[0050] According to the component formula, epoxy resin, polyether modified epoxy resin, defoamer, wetting agent, leveling agent and water are mixed, stirred at 300r / min for 30min, then nano-ceramic heat dissipation filler is added and stirred for 5min, and then curing agent is added and mixed evenly to obtain the nano-ceramic composite coating.
[0051] In Example 3, a composite coating is prepared by including the following components in parts by weight:
[0052] 50 parts by weight of bisphenol A liquid epoxy resin, 8 parts by weight of polyether modified epoxy resin, 20 parts by weight of nano ceramic heat dissipation filler, 0.5 parts by weight of defoamer, 0.3 parts by weight of wetting agent, 0.3 parts by weight of leveling agent, 8 parts by weight of curing agent, and 60 parts by weight of water. The defoamer is BYK-028 defoamer; the wetting agent is BYK-378 wetting agent; the leveling agent is BYK-381 leveling agent; and the curing agent is N-aminoethylpiperazine. The bisphenol A liquid epoxy resin uses epoxy resin E-51, with an epoxy equivalent of 180-200 g / mol and a viscosity (25°C) of 8000-16000 mPa·s.
[0053] The preparation method of the polyether-modified epoxy resin is the same as that in Example 1.
[0054] The preparation method of the nano ceramic heat dissipation filler is the same as that of Example 1.
[0055] The preparation process corresponding to Example 3 comprises the following steps:
[0056] According to the component formula, bisphenol A liquid epoxy resin, polyether modified epoxy resin, defoamer, wetting agent, leveling agent and water are mixed, stirred at 600r / min for 10min, then nano-ceramic heat dissipation filler is added and stirred for 15min, and then curing agent is added and mixed evenly to obtain the nano-ceramic composite coating.
[0057] In Example 4, a composite coating is prepared by including the following components in parts by weight:
[0058] 50 parts by weight of bisphenol A liquid epoxy resin, 15 parts by weight of nano ceramic heat dissipation filler, 0.4 parts by weight of defoamer, 0.15 parts by weight of wetting agent, 0.25 parts by weight of leveling agent, 5 parts by weight of curing agent, and 50 parts by weight of water. The defoamer is BYK-028 defoamer; the wetting agent is BYK-378 wetting agent; the leveling agent is BYK-381 leveling agent; the curing agent is N-aminoethylpiperazine; the bisphenol A liquid epoxy resin uses epoxy resin E-51, the epoxy equivalent is 180-200 g / mol, and the viscosity (25°C) is 8000-16000 mPa·s.
[0059] The preparation method of the nano ceramic heat dissipation filler is as follows: 0.056 parts by weight of lithium hydroxide is mixed with 300 parts by weight of a 45wt% ethanol aqueous solution, 15 parts by weight of hexagonal boron nitride is added under stirring conditions of 700r / min and stirring is continued for 20min, the temperature is raised to 300°C for reaction for 2h, the heating rate is 5°C / min, after the reaction is completed, the mixture is cooled to room temperature, filtered, washed with water until neutral, and vacuum dried to obtain pretreated hexagonal boron nitride; 1.5 parts by weight of pretreated hexagonal boron nitride and 0.2 parts by weight of γ-mercaptopropyltrimethoxysilane are added to 30 parts by weight of a 30wt% isopropanol aqueous solution and ultrasonicated for 20min n, the ultrasonic frequency is 35kHz, the ultrasonic power is 200W, and then 0.5 weight parts of nano aluminum nitride and 0.2 weight parts of carbon nanotubes are added and ball-milled for 12 hours, filtered after the end, and vacuum dried to obtain nitride composite nanoceramics; wherein, the ball milling speed is 500r / min, the ball milling medium is composed of zirconia balls with a diameter of 1mm and zirconia balls with a diameter of 10mm in a mass ratio of 1:0.2, and the ball-to-material ratio is 15:1; the average particle size of the nano aluminum nitride is 50nm; the carbon nanotubes are single-walled carbon nanotubes prepared by chemical vapor deposition, with a tube diameter of 2nm and a tube length of 50μm;
[0060] 3 parts by weight of aluminum nitrate, 1.5 parts by weight of magnesium nitrate, 1.5 parts by weight of zinc nitrate, 0.3 parts by weight of zirconium nitrate and 0.2 parts by weight of yttrium nitrate are added to 200 parts by weight of water and ultrasonicated for 15 minutes at an ultrasonic frequency of 35kHz and an ultrasonic power of 200W, then 25 parts by weight of gluconic acid are added, and the mixture is stirred at 68°C and 120r / min for 120 minutes to evaporate water, and then freeze-dried and heated to 650°C for calcination for 150 minutes at a heating rate of 5°C / min to obtain oxide composite nanoceramics; 2 parts by weight of oxide composite nanoceramics and 1.5 parts by weight of nitride composite nanoceramics are added to 100 parts by weight of Tris buffer (pH 8.5) and ultrasonicated for 40 minutes at an ultrasonic frequency of 35kHz and an ultrasonic power of 200W, and then 1.5 parts by weight of dopamine hydrochloride are added, and the mixture is reacted at 63°C for 18 hours, and then cooled to room temperature, filtered, washed with water until neutral, and vacuum dried to obtain nanoceramic heat dissipation filler.
[0061] The preparation process corresponding to Example 4 comprises the following steps:
[0062] According to the component formula, bisphenol A liquid epoxy resin, defoamer, wetting agent, leveling agent and water are mixed, stirred at 500r / min for 20min, then nano-ceramic heat dissipation filler is added and stirred for 10min, and then curing agent is added and mixed evenly to obtain the nano-ceramic composite coating.
[0063] In Example 5, a composite coating is prepared by including the following components in parts by weight:
[0064] 45 parts by weight of bisphenol A liquid epoxy resin, 5 parts by weight of polyether modified epoxy resin, 15 parts by weight of nano ceramic heat dissipation filler, 0.4 parts by weight of defoamer, 0.15 parts by weight of wetting agent, 0.25 parts by weight of leveling agent, 5 parts by weight of curing agent, and 50 parts by weight of water. The defoamer is BYK-028 defoamer; the wetting agent is BYK-378 wetting agent; the leveling agent is BYK-381 leveling agent; and the curing agent is N-aminoethylpiperazine.
[0065] The preparation method of the polyether modified epoxy resin is as follows: 7.2 parts by weight of bisphenol A liquid epoxy resin and 8 parts by weight of polypropylene glycol monomethyl ether are mixed, 0.12 parts by weight of tetrabutylammonium bromide is added at 60°C under nitrogen protection, the temperature is raised to 105°C for reaction for 7 hours, and the heating rate is 5°C / min to obtain the polyether modified epoxy resin. The bisphenol A liquid epoxy resin adopts epoxy resin E-51, with an epoxy equivalent of 180-200g / mol and a viscosity (25°C) of 8000-16000mPa·s; the polypropylene glycol monomethyl ether has an average molecular weight of 800 and a hydroxyl value of 65-75mgKOH / g.
[0066] The preparation method of the nano ceramic heat dissipation filler is as follows: 3 parts by weight of aluminum nitrate, 1.5 parts by weight of magnesium nitrate, 1.5 parts by weight of zinc nitrate, 0.3 parts by weight of zirconium nitrate and 0.2 parts by weight of yttrium nitrate are added to 200 parts by weight of water, and ultrasonicated for 15 minutes, the ultrasonic frequency is 35kHz, and the ultrasonic power is 200W, then 25 parts by weight of gluconic acid are added, and the water is evaporated at 68°C and 120r / min for 120 minutes, and then freeze-dried, and then heated to 650°C and calcined for 150 minutes, and the heating rate is 5°C / min, so as to obtain the oxide composite nano ceramic; 3.5 parts by weight of the oxide composite nano ceramic is added to 100 parts by weight of Tris buffer (pH is 8.5), and ultrasonicated for 40 minutes, the ultrasonic frequency is 35kHz, and the ultrasonic power is 200W, and then 1.5 parts by weight of dopamine hydrochloride are added, and the reaction is carried out at 63°C for 18 hours, and then cooled to room temperature after the reaction, filtered, washed with water until neutral, and vacuum dried to obtain the nano ceramic heat dissipation filler.
[0067] The preparation process corresponding to Example 5 comprises the following steps:
[0068] According to the component formula, bisphenol A liquid epoxy resin, polyether modified epoxy resin, defoamer, wetting agent, leveling agent and water are mixed, stirred at 500r / min for 20min, then nano-ceramic heat dissipation filler is added and stirred for 10min, and then curing agent is added and mixed evenly to obtain the nano-ceramic composite coating.
[0069] In Example 6, a composite coating is prepared by including the following components in parts by weight:
[0070] 45 parts by weight of bisphenol A liquid epoxy resin, 5 parts by weight of polyether modified epoxy resin, 15 parts by weight of nano ceramic heat dissipation filler, 0.4 parts by weight of defoamer, 0.15 parts by weight of wetting agent, 0.25 parts by weight of leveling agent, 5 parts by weight of curing agent, and 50 parts by weight of water. The defoamer is BYK-028 defoamer; the wetting agent is BYK-378 wetting agent; the leveling agent is BYK-381 leveling agent; and the curing agent is N-aminoethylpiperazine.
[0071] The preparation method of the polyether modified epoxy resin is as follows: 7.2 parts by weight of bisphenol A liquid epoxy resin and 8 parts by weight of polypropylene glycol monomethyl ether are mixed, 0.12 parts by weight of tetrabutylammonium bromide is added at 60°C under nitrogen protection, the temperature is raised to 105°C for reaction for 7 hours, and the heating rate is 5°C / min to obtain the polyether modified epoxy resin. The bisphenol A liquid epoxy resin adopts epoxy resin E-51, with an epoxy equivalent of 180-200g / mol and a viscosity (25°C) of 8000-16000mPa·s; the polypropylene glycol monomethyl ether has an average molecular weight of 800 and a hydroxyl value of 65-75mgKOH / g.
[0072] The preparation method of the nano ceramic heat dissipation filler is as follows: 0.056 parts by weight of lithium hydroxide is mixed with 300 parts by weight of a 45wt% ethanol aqueous solution, 15 parts by weight of hexagonal boron nitride is added under stirring conditions of 700r / min and stirring is continued for 20min, the temperature is raised to 300°C for reaction for 2h, the heating rate is 5°C / min, after the reaction is completed, the mixture is cooled to room temperature, filtered, washed with water until neutral, and vacuum dried to obtain pretreated hexagonal boron nitride; 1.5 parts by weight of pretreated hexagonal boron nitride and 0.2 parts by weight of γ-mercaptopropyltrimethoxysilane are added to 30 parts by weight of a 30wt% isopropanol aqueous solution and ultrasonicated for 20min n, the ultrasonic frequency is 35kHz, the ultrasonic power is 200W, and then 0.5 weight parts of nano aluminum nitride and 0.2 weight parts of carbon nanotubes are added and ball-milled for 12 hours, filtered after the end, and vacuum dried to obtain nitride composite nanoceramics; wherein, the ball milling speed is 500r / min, the ball milling medium is composed of zirconia balls with a diameter of 1mm and zirconia balls with a diameter of 10mm in a mass ratio of 1:0.2, and the ball-to-material ratio is 15:1; the average particle size of the nano aluminum nitride is 50nm; the carbon nanotubes are single-walled carbon nanotubes prepared by chemical vapor deposition, with a tube diameter of 2nm and a tube length of 50μm;
[0073] 3.5 parts by weight of nitride composite nanoceramics were added to 100 parts by weight of Tris buffer (pH 8.5), and ultrasonicated for 40 minutes at an ultrasonic frequency of 35 kHz and an ultrasonic power of 200 W. Then 1.5 parts by weight of dopamine hydrochloride were added, and the reaction was carried out at 63° C. for 18 hours. After the reaction, the reaction was cooled to room temperature, filtered, washed with water until neutral, and vacuum dried to obtain a nanoceramic heat dissipation filler.
[0074] The preparation process corresponding to Example 6 comprises the following steps:
[0075] According to the component formula, bisphenol A liquid epoxy resin, polyether modified epoxy resin, defoamer, wetting agent, leveling agent and water are mixed, stirred at 500r / min for 20min, then nano-ceramic heat dissipation filler is added and stirred for 10min, and then curing agent is added and mixed evenly to obtain the nano-ceramic composite coating.
[0076] In Example 7, a composite coating is prepared by including the following components in parts by weight:
[0077] 45 parts by weight of bisphenol A liquid epoxy resin, 5 parts by weight of polyether modified epoxy resin, 15 parts by weight of nano ceramic heat dissipation filler, 0.4 parts by weight of defoamer, 0.15 parts by weight of wetting agent, 0.25 parts by weight of leveling agent, 5 parts by weight of curing agent, and 50 parts by weight of water. The defoamer is BYK-028 defoamer; the wetting agent is BYK-378 wetting agent; the leveling agent is BYK-381 leveling agent; and the curing agent is N-aminoethylpiperazine.
[0078] The preparation method of the polyether modified epoxy resin is as follows: 7.2 parts by weight of bisphenol A liquid epoxy resin and 8 parts by weight of polypropylene glycol monomethyl ether are mixed, 0.12 parts by weight of tetrabutylammonium bromide is added at 60°C under nitrogen protection, the temperature is raised to 105°C for reaction for 7 hours, and the heating rate is 5°C / min to obtain the polyether modified epoxy resin. The bisphenol A liquid epoxy resin adopts epoxy resin E-51, with an epoxy equivalent of 180-200g / mol and a viscosity (25°C) of 8000-16000mPa·s; the polypropylene glycol monomethyl ether has an average molecular weight of 800 and a hydroxyl value of 65-75mgKOH / g.
[0079] The preparation method of the nano ceramic heat dissipation filler is as follows: 0.056 parts by weight of lithium hydroxide is mixed with 300 parts by weight of a 45wt% ethanol aqueous solution, 15 parts by weight of hexagonal boron nitride is added under stirring conditions of 700r / min and stirring is continued for 20min, the temperature is raised to 300°C for reaction for 2h, the heating rate is 5°C / min, after the reaction is completed, the mixture is cooled to room temperature, filtered, washed with water until neutral, and vacuum dried to obtain pretreated hexagonal boron nitride; 1.5 parts by weight of pretreated hexagonal boron nitride and 0.2 parts by weight of γ-mercaptopropyltrimethoxysilane are added to 30 parts by weight of a 30wt% isopropanol aqueous solution and ultrasonicated for 20min n, the ultrasonic frequency is 35kHz, the ultrasonic power is 200W, and then 0.5 weight parts of nano aluminum nitride and 0.2 weight parts of carbon nanotubes are added and ball-milled for 12 hours, filtered after the end, and vacuum dried to obtain nitride composite nanoceramics; wherein, the ball milling speed is 500r / min, the ball milling medium is composed of zirconia balls with a diameter of 1mm and zirconia balls with a diameter of 10mm in a mass ratio of 1:0.2, and the ball-to-material ratio is 15:1; the average particle size of the nano aluminum nitride is 50nm; the carbon nanotubes are single-walled carbon nanotubes prepared by chemical vapor deposition, with a tube diameter of 2nm and a tube length of 50μm;
[0080] 3 parts by weight of aluminum nitrate, 1.5 parts by weight of magnesium nitrate, 1.5 parts by weight of zinc nitrate, 0.3 parts by weight of zirconium nitrate and 0.2 parts by weight of yttrium nitrate are added to 200 parts by weight of water and ultrasonicated for 15 minutes at an ultrasonic frequency of 35kHz and an ultrasonic power of 200W. Then 25 parts by weight of gluconic acid are added and stirred at 68°C and 120r / min for 120 minutes to evaporate the water. After evaporation, freeze-drying is performed and the temperature is raised to 650°C and calcined for 150 minutes at a heating rate of 5°C / min to obtain oxide composite nanoceramics. 2 parts by weight of oxide composite nanoceramics are mixed with 1.5 parts by weight of nitride composite nanoceramics to obtain nanoceramic heat dissipation filler.
[0081] The preparation process corresponding to Example 7 comprises the following steps:
[0082] According to the component formula, bisphenol A liquid epoxy resin, polyether modified epoxy resin, defoamer, wetting agent, leveling agent and water are mixed, stirred at 500r / min for 20min, then nano-ceramic heat dissipation filler is added and stirred for 10min, and then curing agent is added and mixed evenly to obtain the nano-ceramic composite coating.
[0083] The composite coating in the above embodiment is tested as follows:
[0084] Test Example 1
[0085] The nano-ceramic composite coatings prepared in Examples 1-4 were subjected to performance tests. The adhesion test was conducted according to the cross-hatch method in reference standard GB / T 9286-2021; the salt spray (neutral) test was conducted according to the reference standard GB / T1771-2007; and the water resistance test was conducted according to the immersion method in reference standard GB 5209-1985 (no rust, no blistering, and no shedding, that is, passing). The test results are shown in Table 1.
[0086] Table 1. Basic performance test results of nano-ceramic composite coatings
[0087]
[0088] Test Example 2
[0089] The nano-ceramic composite coating was evenly coated on a PET film, and the wet film thickness was controlled to be 50 μm. After curing, it was completely removed from the PET film and cut into square pieces of strips. The thermal conductivity was measured with reference to the standard ISO22007-2-2008. The normal total radiation emissivity calibration system was used to measure the normal total radiation emissivity of the nano-ceramic composite coatings prepared in the above Examples 1, 5-7 according to the NIM-06-03-2000 operating specification, and was used for the standard blackhead normal total radiation brightness comparison method measurement; the infrared radiometer response wavelength range was 2-18 μm, and the sample temperature was 80°C.
[0090] Table 2. Test results of thermal conductivity and heat dissipation performance of nano-ceramic composite coatings
[0091]
[0092] It can be seen from the above test results that the nano-ceramic composite coatings prepared in Examples 1-3 have good adhesion, salt spray resistance, water resistance, and thermal conductivity and heat dissipation performance. This is because the present invention adds polyether-modified epoxy resin and specific nano-ceramic heat dissipation fillers to the nano-ceramic composite coating, which significantly improves the adhesion, water resistance, and thermal conductivity and heat dissipation performance of the nano-ceramic composite coating.
[0093] It should be noted that, compared with Examples 1-3, Examples 4-7 did not adopt the necessary technical solutions, resulting in obvious deterioration in the corresponding performance tests. Example 4 did not use polyether-modified epoxy resin, and Examples 5-7 did not use nano-ceramic heat dissipation fillers prepared by a specific method. From the results, it can be seen that this leads to a certain degree of decrease in the adhesion, water resistance and thermal conductivity and heat dissipation performance of the nano-ceramic composite coating. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0094] In summary, the implementation of the embodiments of the present invention has the following beneficial effects:
[0095] The composite coating for heat dissipation of box transformers provided by the present invention and the preparation method thereof, by using polyether modified epoxy resin and specific nano ceramic heat dissipation filler in the coating component formula, significantly improves the thermal conductivity and heat dissipation performance of the nano ceramic composite coating, can be used on power distribution equipment such as box transformers, effectively reduce the temperature inside the equipment, and still have good adhesion and salt spray corrosion resistance in harsh outdoor use environments, and can meet the requirements of stability and reliability. The present invention also provides a preparation process for the above nano ceramic composite coating, which is simple.
[0096] The above disclosure is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A composite coating for heat dissipation of box-type transformers, characterized in that: According to weight parts, the preparation includes the following raw materials: 40-50 parts of epoxy resin, 2-8 parts of polyether modified epoxy resin, 10-20 parts of nano ceramic heat dissipation filler, 0.2-0.5 parts of defoaming agent, 0.1-0.3 parts of wetting agent, 0.1-0.3 parts of leveling agent, 2-8 parts of curing agent, and 40-60 parts of water.
2. The composite coating according to claim 1, characterized in that: The polyether-modified epoxy resin is a mixture of epoxy resin, polypropylene glycol monomethyl ether and tetrabutylammonium bromide.
3. The composite coating according to claim 1, characterized in that: The nano ceramic heat dissipation filler is a mixture of oxide composite nano ceramics, nitride composite nano ceramics and dopamine hydrochloride.
4. The composite coating according to claim 1, characterized in that: The curing agent is any one or more of N-aminoethylpiperazine, m-phenylenediamine and diethylenetriamine.
5. A method for preparing a composite coating, for preparing the composite coating for heat dissipation of a box-type transformer as claimed in any one of claims 1 to 4, characterized in that: The steps include: According to the component formula, epoxy resin, polyether modified epoxy resin, defoamer, wetting agent, leveling agent and water are mixed and stirred; After adding the nano-ceramic heat dissipation filler and continuing to stir, the curing agent is added and mixed until uniform, thereby obtaining a composite coating for heat dissipation of the box-type transformer.
6. The method according to claim 5, characterized in that The method also includes mixing 6-8 parts by weight of epoxy resin with 7-10 parts by weight of polypropylene glycol monomethyl ether, adding 0.1-0.2 parts by weight of tetrabutylammonium bromide at a temperature of 60-70° C. under nitrogen protection, heating to 100-110° C., and reacting for 5-10 hours to obtain a polyether-modified epoxy resin.
7. The method according to claim 5, characterized in that Also includes the steps: The lithium hydroxide and the ethanol aqueous solution are mixed, and under stirring conditions, hexagonal boron nitride is added, and the mixture is subjected to a temperature-raising reaction, cooling, filtering, washing with water, and drying in sequence to obtain pretreated hexagonal boron nitride; Pretreated hexagonal boron nitride and γ-mercaptopropyltrimethoxysilane are added to an isopropanol aqueous solution and subjected to ultrasonication, and then nano-aluminum nitride and carbon nanotubes are added and the mixture is ball-milled, filtered, and dried in sequence to obtain a nitride composite nano-ceramic. Aluminum nitrate, magnesium nitrate, zinc nitrate, zirconium nitrate and yttrium nitrate are added to water and ultrasonicated, and then gluconic acid is added and heated, stirred, dried and calcined in sequence to obtain oxide composite nano-ceramics; The oxide composite nano-ceramics and the nitride composite nano-ceramics are added to a buffer solution and ultrasonicated, then dopamine hydrochloride is added and the mixture is heated for reaction, cooled, filtered, washed with water, and dried in sequence to obtain a nano-ceramic heat dissipation filler.
8. The method according to claim 7, characterized in that Also includes the steps: 0.03-0.06 parts by weight of lithium hydroxide and 250-350 parts by weight of a 40-50 wt% ethanol aqueous solution are mixed, 10-20 parts by weight of hexagonal boron nitride are added under stirring, stirring is continued for 15-30 minutes, and the temperature is raised to 290-305° C. for reaction for 1-3 hours; After the reaction is finished, cooling, filtering, washing and drying are performed in sequence to obtain pretreated hexagonal boron nitride; 1-2 parts by weight of pretreated hexagonal boron nitride and 0.1-0.3 parts by weight of γ-mercaptopropyltrimethoxysilane are added to 25-40 parts by weight of isopropanol aqueous solution and ultrasonicated for 15-30 minutes, then 0.4-0.6 parts by weight of nano aluminum nitride and 0.1-0.3 parts by weight of carbon nanotubes are added and ball-milled for 10-15 hours. After the ball-milling is completed, filtering and drying are performed in sequence to obtain nitride composite nano-ceramics.
9. The method according to claim 7, characterized in that Also includes the steps: 2-5 parts by weight of aluminum nitrate, 1-2 parts by weight of magnesium nitrate, 1-2 parts by weight of zinc nitrate, 0.2-0.4 parts by weight of zirconium nitrate and 0.1-0.3 parts by weight of yttrium nitrate are added to 150-300 parts by weight of water and ultrasonicated for 10-20 minutes, then 20-30 parts by weight of gluconic acid are added, stirred for 100-150 minutes at 65-70° C., dried, heated to 600-700° C. and calcined for 130-160 minutes to obtain oxide composite nanoceramics.
10. The method according to claim 7, characterized in that Also includes the steps: 1-3 parts by weight of oxide composite nanoceramics and 1-2 parts by weight of nitride composite nanoceramics are added to 80-120 parts by weight of buffer solution and ultrasonicated for 30-50 minutes, then 1-2 parts by weight of dopamine hydrochloride are added, and the reaction is carried out at 60-65° C. for 15-20 hours, and then the reaction is carried out through cooling, filtering, washing and drying to obtain a nanoceramic heat dissipation filler.